ナンキョク ショウワキチ ニ オケル サブミクロン リュウシ リュウケイ ブンプ ノ キセツ ヘンカ - 長田, 和雄; オサダ, カズオ; 西田, 千春; ニシダ, チハル; 原, 圭一郎; ハラ, ケイイチロウ; 矢吹, 正教; ヤブキ, マサノリ; 塩原, 匡貴; シオバラ, マサタカ; 和田, 誠; ワダ, マコト; et al. (2010)
P(論文) 2004年2月～ 2005年1月にかけて昭和基地で直径5-168 nmの粒径分布を連続観測した.粒径分布は,冬に1～ 2のモードから成り,濃度の高いモードは50 nm以上であることが多く,春～ 夏や秋には2～ 3のモードから成り,濃度の高いモードは20-80 nm付近にあることが多かった.50 nm以上に谷を持つ粒径分布の出現頻度は,開水面が昭和基地に近い夏～ 秋に多かった.一山のみの粒径分布は冬と初夏に多くなり,冬には幅が広く,初夏には幅の狭い分布を示した.初夏から初秋にかけて,10-20 nm付近の核形成モード粒子の濃度が高くなることがあった.11月下旬には,カタバ風の弱くなる午後に核形成モード粒子の濃度が高くなる事例を数日にわたり観測した. Number-size distributions (5-168 nm in diameter) of atmospheric aerosol particles were measured at Syowa Station, Antarctica from February 2004 to January 2005. Size distributions in winter consisted of 1 to 2 modes larger than 50 nm in diameter, whereas 2 to 3 modes contributed to the size distributions in October to March with mode diameters between 20 and 80 nm. Size distribution with a valley at around 50 nm was often observed in summer to fall when the open ocean was located near Syowa Station. From September to March, concentration of ultra fine particles (<20 nm) was occasionally high. Associated with local wind pattern after vertical mixing of boundary layer air in late afternoon, high concentrations of ultra fine particles were observed for several days in late November. departmental bulletin paper